Template-free fabrication of highly-oriented single-crystalline 1D-rutile TiO2-MWCNT composite for enhanced photoelectrochemical activity - Sadhu, Subha; Poddar, Pankaj (Journal of Physical Chemistry C, 2014)
Template-free synthesis of phase pure one-dimensional (1D), single crystalline rutile titania nanorods or wires at low temperature still remains a challenging task due to its complex nature of surface chemistry. In these ID structures, charge transport is highly favored. To further modify the electrical conductivity and optoelectronic properties of these 1D nanostructures, various methods such as doping of TiO2 with metal and nonmetal and synthesis of branched and hybrid structures are developed. If these hybrid structures can directly synthesize on the substrate, the transport of the electron will improve due to reduced grain boundary and exciton recombination. In this contribution, for the first time, we have simultaneously synthesized 1D-rutile TiO2-multiwalled carbon nanotube (MWCNT) composite film directly grown on fluorine dope conducting oxide (FTO) substrate along with 1D-rutile TiO2-MWCNT composite powder. The as-grown nanorods films were single-crystalline and oriented vertically with respect to the substrate, having an average height of similar to 2 mu m. The well connected network of TiO2 with MWCNTs was observed through electron microscopy. The composite film shows positive movement of the flat-band edge and increase in charge carrier density. The TiO2-MWCNT composite was successfully used as photoanode in a dye sensitized solar cell (DSSC) and exhibits a 60% increase in energy-conversion efficiency compared with only TiO2 nanorods.